Frontiers in PROTACs. Issue 10 (October 2021) - Hughes, Gregory R.; Dudey, Ashley P.; Hemmings, Andrew M.; Chantry, Andrew
Highlights: PROTACs hijack the ubiquitin proteasome system to eliminate select disease proteins. Cell permeable peptide PROTACs have been developed to target oncoproteins. Macrocyclic and light controlled PROTACs offer specificity and spatiotemporal control. PROTACs have been developed to act as homo-dimerising compounds to pit E3 ligases against themselves. The PROTAC principle can now be applied to cellular phosphorylation systems. Abstract: Targeting protein–protein interactions (PPI) is a key focus in the development of new and emerging small-molecule therapeutics. Shallow interacting surfaces can render PPI targeting notoriously difficult. This leaves many therapeutically captivating targets 'undruggable'. Despite these challenges, there has been extraordinary progress circumventing this issue by hijacking the ubiquitin proteasome system (UPS) to target selected substrates for destruction using target-based degradation (TBD) strategies, including bifunctional molecules known as proteolysis-targeting chimeras (PROTACs). In this review, we discuss some of the most recent innovative concepts emerging from PROTAC research and related technologies.